2016
DOI: 10.5194/bg-13-4735-2016
|View full text |Cite
|
Sign up to set email alerts
|

Moderate topsoil erosion rates constrain the magnitude of the erosion-induced carbon sink and agricultural productivity losses on the Chinese Loess Plateau

Abstract: Abstract. Despite a multitude of studies, overall erosion rates as well as the contribution of different erosion processes on Chinese Loess Plateau (CLP) remain uncertain, which hampers a correct assessment of the impact of soil erosion on carbon and nutrient cycling as well as on crop productivity. In this paper we used a novel approach, based on field evidence, to reassess erosion rates on the CLP before and after conservation measures were implemented (1950 vs. 2005). We found that current average topsoil e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 73 publications
1
25
0
1
Order By: Relevance
“…It also implies that it remains difficult to assess the overall impact of human activities on overall sediment mobilisation. While several studies have clearly shown that human activities may increase topsoil erosion rates by over two orders of magnitude (Montgomery, 2007;Zhao et al, 2016), the impact of human activities on non-topsoil erosion is much less clear. Human activities have a much smaller effect on the overall sediment transfer from the land to the ocean than on topsoil erosion: studies suggest that the land-ocean sediment transfer would have increased from ca.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…It also implies that it remains difficult to assess the overall impact of human activities on overall sediment mobilisation. While several studies have clearly shown that human activities may increase topsoil erosion rates by over two orders of magnitude (Montgomery, 2007;Zhao et al, 2016), the impact of human activities on non-topsoil erosion is much less clear. Human activities have a much smaller effect on the overall sediment transfer from the land to the ocean than on topsoil erosion: studies suggest that the land-ocean sediment transfer would have increased from ca.…”
Section: Introductionmentioning
confidence: 97%
“…1.37 Gt of sediments to the Bohai Sea, which was ca. 9% of the total global land to sea export: over 90% of these sediments were coming from the CLP (Shi and Shao, 2000;Syvitski et al, 2005;Zhao et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies coupled process-oriented soil erosion models with carbon turnover models calibrated for specific micro-catchments on timescales of a few decades to a millennium, (Billings et al, 2010;Van Oost et al, 2012;Nadeu et al, 2015;Wang et al, 2015a;Zhao et al, 2016;Bouchoms et al, 2017). Other studies focused on the application of parsimonious erosion-SOC-dynamics models using the Revised Universal Soil Loss Equation (RUSLE) approach together with sediment transport methods at regional or continental spatial scales (Chappell et al, 2015;Lugato et al, 2016;Yue et al, 2016;Zhang et al, 2014).…”
mentioning
confidence: 99%
“…One may therefore assume that in these societies erosion rates can be reduced to tolerable levels provided that the necessary policies are maintained and/or strengthened. Countries with a strong central government that can impose decisions on land use and soil conservation, as is the case in China, can successfully reduce erosion: the excessive erosion rates on the Chinese Loess Plateau were strongly reduced through massive government programmes implementing erosion control measures (Chen et al, 2007;Zhao et al, 2016) These approaches are, at present, not possible in most countries of the Global South. Many governments in the Global South are not able to implement a successful soil conservation policy as they do not have at their disposal the necessary data and/or the necessary political and societal instruments to do so.…”
Section: The Way Forwardmentioning
confidence: 99%